Studi Eksperimental Variasi Celah Katup Hisap dan Katup Buang Terhadap Performance Speda Motor 4 Langkah Menggunakan Bahan Bakar Biopremium E10 - sarjono sarjono (SIMETRIS, 2018)
Research has been conducted on experimental studies of the slit Valve's variation in suction valves and exhaust valves against Performance Speda Motor 4 step using the fuel Biopremium E10. The study aims to figure out the performance of a four-step motor spec with a variation of suction valve gaps and exhaust valves using a Biopremium E10 alternative fuel. The results showed that with a suction valve gap of 0.08 mm and a exhaust valve gap of 0.11 mm in the round range of 6000 rpm, the resulting power and torque was the maximum of 9.2 HP and 11.04 Nm, as well as the use of specific fuel effective (SFC) The most economical of 0.0821 kg/kWh